Guardians of the galaxy [videorecording (Blu-Ray)] - Gunn, James, 1966-; Rooker, Michael, 1955-; Diesel, Vin; Hounsou, Djimon, 1964-; Saldana, Zoë, 1978-; Reilly, John C., 1965-; Cooper, Bradley; Pratt, Chris, 1979-; Close, Glenn, 1947-; Toro, Benicio del, 1967- (Marvel Studios, 2017)
Brash adventurer Peter Quill finds himself the object of an unrelenting bounty hunt after stealing a mysterious orb coveted by Ronan, a powerful villain with ambitions that threaten the entire universe. To evade Ronan, Quill is forced into an uneasy truce with a quartet of disparate misfits. But when Quill discovers the true power of the orb and the menace it poses to the cosmos, he must do his best to rally his ragtag rivals for a last, desperate stand-with the galaxy's fate in the balance.